2011
DOI: 10.1007/s10997-011-9191-4
|View full text |Cite
|
Sign up to set email alerts
|

Boards in microfinance institutions: how do stakeholders matter?

Abstract: Microfinance Institutions provide financial services to poor people. Governance of these organizations is important so that they can operate efficiently and sustainably. This study analyzes the influence of stakeholders (donors, employees, customers, and creditors), on board structure (board size and CEO duality), and on organizational performance. We use a global data set of 379 microfinance institutions from 73 countries, collected from rating organizations. Supported by stakeholder theory, agency theory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 63 publications
8
42
1
Order By: Relevance
“…In terms of the enterprise's age, panel A shows a positive relationship between the enterprise's age and the number of employees. This is in line with Mori and Mersland (2014), who suggest that an enterprise's age matters for organizational growth. The results for ownership status suggest that sole proprietorship is negatively associated with YOEs' performance.…”
Section: Econometric Resultssupporting
confidence: 90%
“…In terms of the enterprise's age, panel A shows a positive relationship between the enterprise's age and the number of employees. This is in line with Mori and Mersland (2014), who suggest that an enterprise's age matters for organizational growth. The results for ownership status suggest that sole proprietorship is negatively associated with YOEs' performance.…”
Section: Econometric Resultssupporting
confidence: 90%
“…Prior corporate governance research on listed firms suggests that international corporate influence, such as international directors or foreign listing, is associated with stronger governance mechanisms and may directly enhance firm performance (Ben Naceur, Ghazouani, & Omran, 2007;Oxelheim & Randøy, 2003). Likewise, Mori and Mersland (2014) argue that donor representatives (who in most cases are international ) on MFI boards may have a positive effect on performance.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings show that non-financial stakeholder relationship with the firm has a high and positive effect on firms faced by financial performance challenge rather than on the sustained and superior financial outcome of consolidating business. In the microfinance area, Mori & Mersland (2014) found that a presence of stakeholders on the board of an MFI has a better effect on MFI social and financial performance.…”
Section: Toward a Theoretical Frameworkmentioning
confidence: 99%